PENGARUH TINGKAT PERTUMBUHAN PENJUALAN DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ivanna Simarmata; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to examine the persial and simultaneous influence of the growth rate of sales and capital structure on profitability. Where the independent variables in this study is the level of sales growth and capital structure while the dependent variable is profitability. The sample used is secondary data derived from the financial statements of food and beverage companies listed on the Indonesia Stock Exchange (IDX) period 20011 until 2015.This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Data analysis using multiple linear regression analysis, t test, F test, and test of coefficient of determination. Data analysis using multiple linear regression analysis with SPSS 20.The results of this study indicate that the variable level of sales growth in persial (t test) has no effect on profitability, while the capital structure affect the profitability of food and beverage companies listed on the Indonesia Stock Exchange. Simultaneous test results (f) show the influence of the variable growth rate of sales and capital structure on profitability in food and beverage companies listed on the Indonesia Stock Exchange.Keywords: level of Sales Growth, Capital Structure (DER), and Profitability(ROE).